2002
DOI: 10.1046/j.1469-0705.2002.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cycle‐to‐cycle variation of endometrial responsiveness using transvaginal sonography in women undergoing assisted reproduction

Abstract: It is possible to predict the occurrence of optimal or suboptimal endometrial response in natural cycles of women, after evaluation in stimulated cycles, with a high degree of reliability. Risk of implantation failure can be identified before subsequent treatment cycles and adjuvant therapeutic strategies may be planned to improve the endometrial response before embryo transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 22 publications
2
49
0
4
Order By: Relevance
“…Primary outcome measures [1] were endometrial lining thickness on the baseline day after pituitary suppression with GnRH-a and 5 days before gonadotropin initiation (EMT Baseline ), [2] on day 6 of gonadotropin stimulation (EMT Day 6 ), [3] on the day of hCG administration (EMT hCG ), [4] the change in endometrial thickness from the EMT Baseline to EMT Day 6 (⌬EMT Day 6 -Baseline ), [5] the change in endometrial thickness from the EMT Day 6 to EMT hCG (⌬EMT hCG -Day 6 ), and [6] the change in endometrial thickness from the EMT Baseline to EMT hCG (⌬EMT hCG -Baseline ).…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary outcome measures [1] were endometrial lining thickness on the baseline day after pituitary suppression with GnRH-a and 5 days before gonadotropin initiation (EMT Baseline ), [2] on day 6 of gonadotropin stimulation (EMT Day 6 ), [3] on the day of hCG administration (EMT hCG ), [4] the change in endometrial thickness from the EMT Baseline to EMT Day 6 (⌬EMT Day 6 -Baseline ), [5] the change in endometrial thickness from the EMT Day 6 to EMT hCG (⌬EMT hCG -Day 6 ), and [6] the change in endometrial thickness from the EMT Baseline to EMT hCG (⌬EMT hCG -Baseline ).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Understanding these factors can help in counseling patients regarding their chances of success and in offering interventions for improvement. Factors of both embryologic development and endometrial differentiation have been evaluated (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). With respect to endometrial differentiation, the possible predictors of pregnancy that have been evaluated are endometrial blood flow, endometrial pattern, and endometrial thickness (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…An adequate thickness of endometrium is indispensable for a successful pregnancy [4][5][6]. Some investigators demonstrated that an endometrial thickness less than 8 mm resulted in significantly lower implantation and pregnancy rates [7,8], although others reported different cutoff values between 7 and 10 mm [9]. In addition to the low pregnant potential, thin endometrium is also correlated with a higher risk of miscarriage [10].…”
Section: Introductionmentioning
confidence: 99%
“…A thick endometrium is associated with a higher rate of successful pregnancy, live births, and ongoing pregnancy compared with women with thin endometria (Zhang et al, 2005). It is thought that a prerequisite of successful embryo implantation is the thickness of the endometrium: more than 6 mm and preferably 7-8 mm (Basir et al, 2002;Bodri et al, 2007). Therefore, a thicker endometrium aids a successful pregnancy.…”
Section: Introductionmentioning
confidence: 99%